2018
DOI: 10.1093/gerona/gly040
|View full text |Cite
|
Sign up to set email alerts
|

The Contributions of Fiber Atrophy, Fiber Loss, In Situ Specific Force, and Voluntary Activation to Weakness in Sarcopenia

Abstract: The contributions of fiber atrophy, fiber loss, in situ specific force, and voluntary activation to weakness in sarcopenia remain unclear. To investigate, 40 older (20 women; age 72 ± 4 years) and 31 younger adults (15 women, age 22 ± 3 years) completed measurements. The knee extensor maximal voluntary torque (MVC) was measured as well as voluntary activation, patella tendon moment arm length, muscle volume, and fascicle architecture to estimate in situ specific force. Fiber cross-sectional area (FCSA), fiber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
79
4
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(95 citation statements)
references
References 48 publications
4
79
4
3
Order By: Relevance
“…These features of muscle architecture and motor unit activation also change as part of the ageing process and, after accounting for these changes, it is possible to estimate the 'muscle quality' as strength per unit muscle mass (known as 'in situ specific force'). A recent study showed that this measurement of muscle quality was reduced by 17% in older adults' quadriceps compared with younger adults (McPhee et al, 2018), and this corresponds closely with a 16% lower specific tension reported for single muscle fibres (Brocca et al, 2017). A five-year follow-up of the older participants revealed accelerated declines in muscle mass and strength through the eighth decade compared with estimates of changes made from age 30-70 years (McPhee et al, 2018).…”
Section: Muscle Quality and Quantitysupporting
confidence: 54%
See 1 more Smart Citation
“…These features of muscle architecture and motor unit activation also change as part of the ageing process and, after accounting for these changes, it is possible to estimate the 'muscle quality' as strength per unit muscle mass (known as 'in situ specific force'). A recent study showed that this measurement of muscle quality was reduced by 17% in older adults' quadriceps compared with younger adults (McPhee et al, 2018), and this corresponds closely with a 16% lower specific tension reported for single muscle fibres (Brocca et al, 2017). A five-year follow-up of the older participants revealed accelerated declines in muscle mass and strength through the eighth decade compared with estimates of changes made from age 30-70 years (McPhee et al, 2018).…”
Section: Muscle Quality and Quantitysupporting
confidence: 54%
“…First, there is a reduction of the average muscle fibre cross-sectional area, particularly affecting the larger and more powerful type 2 fibres. On average, these account for approximately 55% of total vastus lateralis (one of the four quadricep muscles) muscle fibre area in younger people and they atrophy by around 25% in older age (McPhee et al, 2018). Muscle fibres of older people also show increased variability of size with some small, angular fibres and some enclosed fibres, which are hallmarks of cycles of denervationreinnervation (Fig.…”
Section: Muscle Quality and Quantitymentioning
confidence: 99%
“…Ageing is associated with an overall reduction in skeletal muscle mass that contributes significantly to the loss of muscle strength [4]. This loss of strength and concomitant slowing of the muscle [34] result in an age-related reduction in muscle power that is associated with a reduced performance in the timed-up-and-go and 6-min-walking test [35].…”
Section: Longitudinal Age-related Decline In Muscle Mass In Older Peoplementioning
confidence: 99%
“…This loss of muscle mass and physical function has been described as sarcopenia [2]. By the eighth decade, muscle mass has declined by around 30% from peak values, with these losses principally coming from the atrophy of type II fibres [3] and loss of muscle fibres [4]. The loss of myofibers is thought to be a consequence of motor neuron death and it has been reported that up to 50% of motor units are lost by the eighth decade [5].…”
Section: Introductionmentioning
confidence: 99%
“…It follows, therefore, that underlying causes of sarcopenia might also contribute to frailty. Sarcopenia is attributable to a decrease in the cross‐sectional area (atrophy) of individual muscle fibres and a decrease in the numbers of muscle fibres (McPhee et al., ; Wilkinson, Piasecki, & Atherton, ). These muscle changes are associated with declining numbers of motor neurons and functioning motor units (MUs; Piasecki et al., ,c; Piasecki, Ireland, Jones, & McPhee, ).…”
Section: Introductionmentioning
confidence: 99%